Administration of Lactobacillus paracasei strains improves immunomodulation and changes the composition of gut microbiota leading to improvement of colitis in mice. (January 2019) - Kim, Woon-Ki; Jang, You Jin; Seo, Boram; Han, Dae Hee; Park, SungJun; Ko, GwangPyo
Graphical abstract: Highlights: L. paracasei modulates cytokines and T regulatory cells in an in vivo model. L. paracasei has protective effects on intestinal tight junctions and mucus layers. L. paracasei treatment alters the diversity and composition of gut microbiota. L. paracasei could be effective in preventing inflammatory bowel disease. Abstract: We confirmed that Lactobacillus paracasei ( L. paracasei ) strains (KBL382, 384, 385) exhibited strong protective effects in an in vivo dextran sodium sulfate-induced colitis model. L. paracasei treatment significantly improved colitis symptoms. Among tested strains, L. paracasei KBL382-treated mice exhibited significantly lower levels of cytokines interferon gamma, interleukin (IL)-4, IL-6, tumor necrosis factor, and IL-17A. On the other hand, higher levels of anti-inflammatory cytokine IL-10 and CD4 + CD25 + Foxp3+ T regulatory cell populations in mesenteric lymph nodes were observed in mice group with L. paracasei . L. paracasei treatment clearly increased zonula occluden-1, claudin 3, and mucin 4 levels, which improved the tight junction and mucus thickness. L. paracasei -treated mice showed significantly higher bacterial diversity and changed the composition of cecal microbiota. Therefore, we suggest that L. paracasei could be a useful tool in the treatment of inflammatory bowel diseases via immunomodulation and the improvement of gut microbiota.